Human mental workload : models and applications : third International Symposium, H-WORKLOAD 2019, Rome, Italy, November 14-15, 2019, Proceedings /: models and applications : third International Symposium, H-WORKLOAD 2019, Rome, Italy, November 14-15, 2019, Proceedings. (2019) - Unknown
No abstract available